Psychotherapeutic case formulation: Plan analysis for narcissistic personality disorder. (17th June 2021) - Grandjean, Loris; Hummel, Jana; Wyer, Dominik; Beuchat, Hélène; Caspar, Franz; Sachse, Rainer; Berger, Thomas; Kramer, Ueli
Abstract: Background: One of the relevant case formulation methods for personality difficulties is plan analysis. The present study aimed at delivering a prototypical plan analysis for clients presenting with a diagnosis of narcissistic personality disorder (NPD). The sample consisted of 14 participants diagnosed with an NPD. Based on audio clinical material, we developed 14 individual plan analyses that we then merged into a single prototypical plan analysis. For explorative purposes, we ran an ordinary least squares regression model to predict the narcissistic symptoms severity (NAR) measured on a scale of 1–7 of the 14 clients by the presence (respectively absence) of certain plans in their individual plan analysis. The synthesis revealed that clients with pathological narcissism share common basic motives. Results of the regression model reveal that the presence of the plan 'be strong' reduces the NAR scale by 1.52 points ( p  = 0.011). Discussion: In the treatment of psychological disorders, precise case formulations allow therapists for making clinically appropriate decision, personalizing the intervention and gaining insight into the client's subjective experience. In the prototypical plan structure we developed for NPD, clients strive to strengthen their self‐esteem and avoid loss of control, criticism and confrontation as well as to get support, understanding and solidarity. When beginning psychotherapy with a client presenting with NPD, the therapist can use these plans as valuable information to help writing tailored, and therefore more efficient, case formulations for their patients presenting with an NPD.